Penerapan Teknologi Augmented Reality Sebagai Media Pembelajaran Aksara Jawa Untuk Siswa Kelas 3 di SDN Jenang 01 - Riadi Windika; Novian Adi Prasetyo; Shintia Dwi Alika (Universitas Andalas, 2022)
Javanese script is a part of Javanese culture which is owned by Javanese society which should be preserved. One of the efforts to preserve it is by introducing Javanese script in formal education. Javanese language subjects are local content that must be taken by students from grade I to grade VI elementary school students. Javanese script began to be introduced to third grade elementary school students. Javanese script is one of the basic competencies that most students do not understand because most students consider Javanese script a difficult material to learn because of its various forms and complicated writing rules. Therefore, to overcome the above problems, a learning innovation using augmented reality technology is needed. With this application, it is hoped that students can be helped in understanding Javanese script material. Java script learning applications are made using the Waterfall method with the development of augmented reality, namely marker based tracking. The output of this application is that the application will display a video on the smartphone screen that contains learning material for Javanese script. In the black box test results on functional testing obtained a percentage of 99.7%, camera distance testing obtained 66.25% results, camera angle testing obtained 75% results, light intensity testing obtained 100% results. In the usability test results, the Carakan application obtained an adjective rating of 71.54 in the Good category, obtained a grade scale result in the C category, and obtained acceptability ranges in the acceptable category.